Experimental characterization of a 1 kW Helicon Plasma Thruster. (March 2018) - Navarro-Cavallé, J.; Wijnen, M.; Fajardo, P.; Ahedo, E.
Abstract: A Helicon Plasma Thruster has been tested in the 500-1000 W radio-frequency power range, at 13.56 MHz. In order to determine its propulsive performances, a parametric study of some operational parameters has been carried out, including the exploration of the magnetic field topology and strength, the mass flow rate, and different propellants. The plasma plume has been characterized by means of intrusive plasma diagnostics, which allow an indirect estimation of the thrust, 2-6.6 mN, and thrust efficiency, about 2.9%. The structure of the plasma expansion is compared against a theoretical model showing a good agreement. Highlights: A Helicon Plasma Thruster (HPT) has been tested successfully under vacuum conditions, 2.5 10e-5 mbar. The ion beam divergence of the HPT has been estimated above 50 deg. The plasma structure throughout the expansion shows a good agreement with the theoretical results. HTP propellant utilization is measured, 20% at 900 W and 1.5 mg/s of Argon. HPT thrust efficiency is indirectly estimated about 2.9%, at 500 W and 1.5 mg/s of Argon.